Transition to Professional Practice in the United States: Exploring the Experiences of Internationally Educated Nurses - Porter, Marlene T.; Williams, Kate; Gembol, Leslie (The Journal of continuing education in nursing, 2024)
Background Many countries facing workforce shortages rely on internationally educated nurses (IENs) to supplement the nursing workforce. The goal of this study is to investigate the experiences of IENs during the peak of their acculturation to their new environment. Method A descriptive qualitative approach was used with focus groups conducted 6 to 9 months after the IENs' start date. Purposive sampling was used to recruit participants at a large academic hospital. Focus groups were conducted in person, audiorecorded, and transcribed. Data were analyzed with reflexive thematic analysis. Results Twenty-seven subjects participated in the focus groups. Three key themes were identified to describe the experiences: (a) navigating the challenging journey, (b) unlearning-relearning nursing practice, and (c) adapting to the work environment. Conclusion This study was the first to examine IENs' experiences 6 to 9 months after arriving in the United States. Study findings show the importance of developing transition programs to support this population of nurses. [J Contin Educ Nurs. 2024;55(12):568–574.]